Assessing a Digital Public Health Intervention: Survey Implementation and Analysis in Washington State Using an Address-Based Sample - Elder, Adam S.; Molino, Andrea R.; Hills, Rebecca A.; Revere, Debra; Baumgartner, Chris; Karras, Bryant T.; Baseman, Janet G. (ACI Open, 2025)
In November 2021, the Washington State Department of Health launched WA Verify, a quick-response (QR) code-based tool that allows users to share their coronavirus disease 2019 (COVID-19) vaccine status using a mobile phone.This study aimed to gather an unbiased sample of Washington residents to collect information about their experiences and opinions on digital public health interventions, with a particular focus on WA Verify.The WA Verify evaluation team designed and implemented a statewide survey using an address-based sample to assess respondents' knowledge, attitudes, and practices regarding COVID-19, WA Verify, and technology. To facilitate comparisons with known characteristics of the Washington State population, the survey included questions also found in state and national surveys and the U.S. Census. Weights based on demographic characteristics were developed to allow for weighted analyses in the future.The unweighted demographic distribution of respondents mostly matched that of the Washington State population, with the largest discrepancy in education; 58.9% of respondents reported having a four-year degree or higher versus 37.3% of the state population. Across race, education level, age and gender, there were differences in reported experiences with and views on requirements to provide vaccination verification and awareness and use of WA Verify.Despite differences in experiences and views on WA Verify, there is broad interest in the tool, suggesting opportunities to expand its adoption. Data and information gathered with this survey, conducted using an address-based sample, provide a strong foundation for further analyses to inform public health interventions, particularly informatics-focused projects.
Keywords: smart phone; Electronic health records and systems; information assurance; public health; statistical methods; General information systems and technologies in clinical settings